Jerry Falwell and the rise of the religious right : a brief history with documents - Sutton, Matthew Avery, 1975- (Boston : Bedford/St. Martins, 2013)
"As one of the most media-savvy ministers in U.S. history, Jerry Falwell figured prominently in the political mobilization of religious conservatives in the 1970s and early 1980s. Falwell's life and work touched on almost all of the major issues of the time period: the cold war, changing gender roles, civil rights, the revitalization of American conservatism, and the Reagan revolution. In his introductory essay, Matthew Avery Sutton traces Falwell's politicization and rise to celebrity status, using Falwell as a lens through which to view the larger movement. More than two dozen primary documents focus on the Religious Right's emergence in the 1970s as a powerful political force and present students with first-hand accounts of the era's culture wars. The thematically arranged documents including sermons, letters, speeches, interviews, court documents, and children's books provide an up-close look at the motivations and aspirations of the Religious Right. Photographs, document headnotes, a chronology, questions for consideration, and a selected bibliography provide additional pedagogical support."--Publisher description.
Pt. 1. Introduction: evangelicals and the reconstruction of American politics and culture. Making Jerry Falwell ; The origins of American fundamentalism ; Remaking American evangelicalism ; Race and the politicalization of American evangelicals ; Focusing on the family ; building the religious right ; The moral majority and the Reagan revolution ; Beyond the moral majority -- pt. 2. The documents. Modern evangelicalism comes of age: The "new" evangelicalism, 1957 / Harold John Ockenga ; America at the crossroads, 1958 / Billy Graham ; The late great planet earth, 1970 / Hal Lindsey ; Chicago declaration of evangelical social concern, November 25, 1973 ; A Christian manifesto, 1981 / Francis Schaeffer -- Race and religious activism: A Southern evangelical on integration, August 17, 1955 / L. Nelson Bell ; A minister denounces the Civil Rights Act, March 26, 1964 / Carl McIntire ; Ministers and marches, 1965 / Jerry Falwell ; Bob Jones University v. United States, 1981, 1983 ; Down with the honky Christ, January 30, 1976 / Clarence Hilliard -- The battle for the schools: Engel v. Vitale and the end of official school prayer, 1962 ; A Christian view of radical sex education, 1969 / Tim LaHaye ; The benefits of Lynchburg Christian Academy, 1975 ; God in American history, 1977 / Peter Marshall and David Manuel ; Dinosaurs and young-earth creationism, 1977 / Duane Gish -- Focusing on the family: Abortion: an evangelical view, February 1971 / Carl F.H. Henry ; The House debates "pro-life" civil disobedience, 1985, 1986 ; When the homosexuals burn the Holy Bible in public...how can I stand by silently, ca. 1977 / Anita Bryant ; Homosexuality: is it an acceptable lifestyle? 1978 / Jerry Falwell ; The total woman, 1973 / Marabel Morgan ; Interview with Phyllis Schlafly on the Equal Rights Amendment, November 1978 -- God and the GOP: Action plan for the 1980s, 1979 / Pat Robertson ; Organizing the moral majority, 1980 / Jerry Falwell ; Evangelicals share their concerns with President Jimmy Carter, January 21, 1980 ; Remarks at the annual convention of the National Association of Evangelicals, March 8, 1983 / Ronald Reagan ; Remarks at an ecumenical prayer breakfast in Dallas, Texas, August 23, 1984 / Ronald Reagan ; A pornographer's eulogy for Jerry Falwell, May 20, 2007 / Larry Flynt -- Appendixes: A chronology of the religious right (1925-2007) ; Questions for consideration ; Selected bibliography.
Includes bibliographical references (p. 148-150) and index.
Keywords: Falwell, Jerry; Christianity and politics -- United States -- Sources; Church and state -- United States -- Sources; Religious right -- United States -- Sources; Christianity and politics -- United States -- History -- 20th century -- Sources